Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.2332/allergolint.55.149
|View full text |Cite
|
Sign up to set email alerts
|

Cough Sensitivity in Pure Cough Variant Asthma Elicited Using Continuous Capsaicin Inhalation

Abstract: The cough sensitivity of patients with cough variant asthma is not necessarily identical to that of healthy individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…We conclude that airway afferent nerve endings reactivity in asthmatic subjects was significantly increased compared with healthy volunteers. Our data about increased CRS in asthmatics are consistent with data of other studies (10,12).…”
Section: Discussionsupporting
confidence: 95%
See 3 more Smart Citations
“…We conclude that airway afferent nerve endings reactivity in asthmatic subjects was significantly increased compared with healthy volunteers. Our data about increased CRS in asthmatics are consistent with data of other studies (10,12).…”
Section: Discussionsupporting
confidence: 95%
“…Patients with asthma have an increased sensitivity to capsaicin which is most marked in those who complain of cough (10). Nakajima et al (12) showed that in asthmatics in whom cough is the sole or predominant symptom, CRS is significantly enhanced.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…For instance, inhaled capsaicin provokes exaggerated cough response in patients with cough variant, but not classic, asthma ( Fig. 31B; Nakajima et al, 2006), as well as in sensory airway hyper-reactivity syndrome (SHR) (Ternesten-Hassèus et al, 2013). Indeed, the capsaicin inhalation test is broadly used as a diagnostic tool to identify patients with SHR (Johansson et al, 2002).…”
Section: B Transient Receptor Potential Channels Inmentioning
confidence: 99%